Disease burden of breast cancer and risk factors in Europe 44 countries, 1990-2019: findings of the global burden of disease study 2019 - Yu, Shaohong; Cai, Xiuli; Wang, Xinyu; Lin, Xiuquan; Cai, Shuanglong (Frontiers in Endocrinology, 2024)
Background Breast cancer (BC) represents a significant health challenge in Europe due to its elevated prevalence and heterogeneity. Despite notable progress in diagnostic and treatment methods, the region continues to grapple with rising BC burdens, with comprehensive investigations into this matter notably lacking. This study explores BC burden and potential contributing risk factors in 44 European countries from 1990 to 2019. The aim is to furnish evidence supporting the development of strategies for managing BC effectively.Methods Disease burden estimates related to breast cancer from the Global Burden of Disease 2019(GBD2019) across Eastern, Central, and Western Europe were examined using Joinpoint regression for trends from 1990 to 2019. Linear regression models examined relationships between BC burden and Socio-demographic Index (SDI), healthcare access and quality (HAQ), and BC prevalence. We utilized disabilityadjusted life year(DALY) proportions for each risk factor to depict BC risks.In Europe, the BC burden was 463.2 cases per 100,000 people in 2019, 1.7 times the global burden. BC burden in women was significantly higher and increased with age. Age-standardized mortality and DALY rates of BC in Europe in 2019 decreased by 23.1%(average annual percent change: AAPC -0.92) and 25.9%(AAPC -1.02), respectively, compared to 1990, in line with global trends. From 1990 to 2019, age-standardized DALY declined faster in Western Europe (-34.8%, AAPC -1.49) than in Eastern Europe (-9.4%, AAPC -0.25) and Central Europe (-15.0%, AAPC -0.56).Monaco, Serbia, and Montenegro had the highest BC burden in Europe in 2019. BC burden was negatively correlated with HAQ. In addition, Alcohol use and Tobacco were significant risk factors for DALY. High fasting plasma glucose and obesity were also crucial risk factors that cannot be ignored in DALY.The burden of BC in Europe remains a significant health challenge, with regional variations despite an overall downward trend. Addressing the burden of BC in different regions of Europe and the increase of DALY caused by different risk factors, targeted prevention measures should be taken, especially the management of alcohol and tobacco should be strengthened, and screening services for BC should be popularized, and medical resources and technology allocation should be optimized.